A companion to Ronald Reagan - Johns, Andrew L., 1968- (Malden, MA ; Chichester, West Sussex, UK : Wiley Blackwell, 2015)
A Companion to Ronald Reagan evaluates in unprecedented detail the events, policies, politics, and people of Reagan's administration. It assesses the scope and influence of his various careers within the context of the times, providing wide-ranging coverage of his administration, and his legacy.
Introduction: to grasp and hold a vision: Ronald Reagan and his times / Andrew L. Johns -- Part I. Ronald Reagan's pre-presidential life and career -- Reagan's early years: from Dixon to Hollywood / John Sbardellati -- Political ideology and activism to 1966 / Lori Clune -- Reagan's gubernatorial years: from conservative spokesperson to national politician / Kurt Schuparra -- Reagan runs: his campaigns for the presidency, 1976, 1980, and 1984 / Yanek Mieczkowski -- Part II. The Reagan administration, 1981-1989 -- Domestic policy: politics & economics -- The great communicator: rhetoric, media, and leadership style / Reed L. Welch -- Reagan and the evolution of American politics, 1981-1989 / Andrew E. Busch -- Ronald Reagan and the Supreme Court / Andrew E. Hunt -- Reaganomics: the fiscal and monetary policies / W. Elliot Brownlee -- Reagan and the economy: business and labor, deregulation and regulation / Michael Adamson -- Reagan and the military / Jonathan Reed Winkler -- Domestic policy: social & cultural issues -- Ronald Reagan, race, civil rights, and immigration / Lilia Fernandez -- Reagan, religion, and the culture wars of the 1980s / Matthew Avery Sutton -- Reagan and aids / Jennifer Brier -- The crackdown in America: the Reagan revolution and the war on drugs / Jeremy Kuzmarov -- Ronald Reagan's environmental legacy / Jacob Darwin Hamblin -- Foreign policy: issues -- Reagan, the Soviet Union, and the Cold War, 1981-1985 / Michael V. Paulauskas -- Shaking the empire or a negotiated settlement: Ronald Reagan and visions of the Cold War's end / Gregory Mitrovich -- The Iran-ConTra Affair / James F. Siekmeier -- The Reagan Doctrine / Dustin Walcher -- Reagan and terrorism / Heather S. Gregg -- Foreign policy: regions -- Reagan and Africa / James H. Meriwether -- Reagan and Western Europe / William Glenn Gray -- Reagan and Asia / Michael Schaller -- Reagan and Central America / Jason M. Colby -- Reagan and the Middle East / Clea Bunch -- Key figures -- Mikhail Gorbachev / Elizabeth C. Charles -- The vice presidency of George H.W. Bush / Michael F. Cairo -- Ronald Reagan, Tip O'Neill, and 1980s congressional history / Robert David Johnson -- The troika: James Baker III, Edwin Meese III, and Michael Deaver / Christopher Maynard -- A foreign policy divided against itself: George Shultz vs. Caspar Weinberger / Andrew Preston -- Margaret Thatcher / Michael F. Hopkins -- Part III. The legacy of Ronald Reagan -- Reagan and the conservative movement / Sandra Scanlon -- Reagan and globalization / Thomas W. Zeiler -- Reputation and legacies: an American symbol / Chester Pach.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Reagan, Ronald; Reagan, Ronald; Reagan, Ronald; 1981-1989; HISTORY / United States / State & Local / General; Diplomatic relations; Politics and government; United States -- Politics and government -- 1981-1989.; United States -- Foreign relations -- 1981-1989.; United States; Electronic books; Electronic books